單複相證的詞義學依據及其在《廣雅疏證》中的運用: Basis which the Word Meaning Study in the Verification by Mono-/Di-syllables and its Use in Guangya Shuzheng (廣雅疏證) - 張, 其昀 (人文中國學報, 2010)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 單複相證是指以字面相關的單音詞與複音詞相互證義。單複相證之詞義學依據在於：單複可以同義。單複相證是《廣雅疏證》的一種一般性證義手段。書中單複相證共使用了“重言”、“合言”和“單言”三個術語。 The verification by mono-/di-syllables is the circumstance where monosyllables and disyllables containing a same character verify each other. The verification by mono-/di-syllables has the basis which the word meaning study, this is: word meaning of mono-/di-syllables possible same. The verification by mono-/di-syllables is a commonly used in Guangya Shuzheng (廣雅疏證). This method altogether has utilized chongyan (重言), heyan (合言), and danyan (單言) these three terminology in the book.